Use of simulation and wear prediction to explore design improvements to the cup seal in the India Mark II/III hand pump system. (2022) - Ottosson, Hans J.; Mattson, Christopher A.; Johnson, Oliver K.; Irot, Immy
Abstract: The India Mark II/III hand pump system is now over 40 years old and has become a staple in how water is retrieved in many rural areas across India and Africa. With over 4 million installations, it is estimated that 10% of the world's population is using one on a daily basis. One of the components that fails most frequent is the nitrile cup seal found in the under-ground pump cylinder, often causing the pump to become derelict for undesirably long periods of time. This paper's focus is on this cup seal and how the wear and life of the seal can be predicted. A test rig was created to evaluate and test cup seals. From this, seal performance and the nitrile cup seal wear coefficient were found. A two-dimensional finite element model of the seal and the pump cylinder was then developed and used to calculate the pressure distribution and wear of the seal. Archard's wear law was used to simulate the wear. From this, models for pump performance and seal wear prediction were created. This data was then used to explore possible design improvements to the cup seal. By combining this data with engineering tools such as ANSYS, MATLAB, and JMP, a new seal design was generated that has the potential to last 12% longer than the original cup seal.